Electrolyte additive and application thereof in alkali metal-thionyl chloride secondary battery
By introducing benzene sulfoxide organic matter as electrolyte additives in alkali metal-thionyl chloride secondary batteries, the redox medium characteristics are used to solve the problems of voltage hysteresis and difficulty in charging, and efficient discharge and secondary cycle of the battery are achieved.
Patent Information
- Application Number
- CN202311291683.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-08
- Publication Date
- 2025-04-08
AI Technical Summary
Alkaline metal-thionyl chloride secondary batteries have problems of voltage hysteresis and difficulty in charging. The prior art has failed to simultaneously improve discharge and reversibility by developing electrolyte additives with redox media.
Benzene sulfoxide organic compounds are introduced as electrolyte additives, and the discharge and charging performance of the battery is improved through its redox media characteristics.
It effectively increases the discharge voltage of the battery, withstands large-scale discharge, significantly reduces the charge and discharge polarization, realizes the secondary stable cycle of the battery, and significantly improves the retention rate of the cycle capacity.
Smart Images

Figure CN119786760A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energy materials and devices, more specifically to the field of alkali metal batteries, and specifically relates to an electrolyte additive and application thereof in alkali metal-thionyl chloride secondary batteries. Background Art
[0002] In recent years, the rapid growth of the global economy and the trend of energy transformation have created a huge demand for clean energy with high energy density, high safety and high stability. It is particularly important to develop new batteries to address the bottleneck problems currently faced by lithium-ion battery research and development. Alkali metal-thionyl chloride primary batteries have aroused widespread research interest due to their high energy density (>700Wh / Kg), high safety (not easy to self-discharge, shelf life can reach 10-20 years), stable discharge voltage, wide temperature operating range (from -60℃ to 150℃), and mature commercial systems.
[0003] Take the lithium-thionyl chloride (Li-SOCl2) battery as an example. For its discharge mechanism, SOCl2 acts as both an electrolyte solvent and a discharge active substance. SOCl2 adsorbed on the positive electrode carbon obtains electrons and is reduced to sulfur, sulfur dioxide and chloride ions. Some sulfur and sulfur dioxide can be dissolved in the thionyl chloride electrolyte, while chloride ions combine with lithium ions dissolved from the lithium negative electrode to form lithium chloride and deposit on the carbon. The specific reaction formula is: 4Li + +4e - +2SOCl2→4LiCl+S+SO2↑. In terms of primary discharge, alkali metal-thionyl chloride batteries have problems with poor rate performance and voltage hysteresis. The former is due to the dimerization of thionyl chloride free radicals produced by reduction, which hinders subsequent reduction, and the latter is due to the excessive impedance caused by excessive densification of lithium chloride. At present, large conjugated system additives such as metal porphyrins and phthalocyanines are usually introduced, which can improve the rate by adsorbing thionyl chloride to enhance reduction and avoid dimerization; at the same time, they can adsorb lithium ions to avoid excessively dense deposition at the carbon interface to increase the discharge potential and capacity.
[0004] The charging mechanism is currently recognized to be a chlorine-mediated reaction pathway. Specifically, the lithium chloride deposited on the carbon decomposes into chlorine (2LiCl-2e - →2Li ++Cl2↑), chlorine will react with the aforementioned products of sulfur and sulfur dioxide to form sulfur dichloride (Cl2+S→SCl2) and sulfuryl chloride (Cl2+SO2→SO2Cl2), and the two are combined to be converted into thionyl chloride (SCl2+SO2Cl2→2SOCl2) through the neutralization reaction, which is reversible. But in fact, the reaction pathway mediated by chlorine is difficult to convert, so it cannot be a secondary battery, that is, it is not rechargeable. However, recently, based on the perspective of regulating the positive electrode structure and protecting the negative electrode interface, researchers (Nature 596,525-530,2021; JACS 144,22505-22513,2022; Joule 7,515-528,2023) have successfully realized a reversible alkali metal-chlorine battery based on thionyl chloride (a reversible alkali metal-thionyl chloride battery in a non-traditional sense). However, the system subsequently uses chlorine as the redox couple and no longer involves the reaction of thionyl chloride.
[0005] At present, there is no research on developing electrolyte additives with redox mediators to improve discharge and reversibility at the same time, that is, introducing additives to achieve high-power secondary batteries. Therefore, it is of great significance to develop new additives for alkali metal-thionyl chloride secondary batteries. Summary of the invention
[0006] In order to solve the problems of voltage hysteresis and difficulty in charging of alkali metal-thionyl chloride secondary batteries, the present invention provides an electrolyte additive and application thereof in alkali metal-thionyl chloride secondary batteries.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] An electrolyte additive for an alkali metal-thionyl chloride secondary battery. The additive in the electrolyte for the alkali metal-thionyl chloride secondary battery is an organic substance containing phenyl sulfoxides; the concentration of the additive in the electrolyte is 0.05-1.0 mol / L, preferably 0.1-0.5 mol / L.
[0009] The phenyl sulfoxide organic compound is one or more of diphenyl sulfoxide, N-sulfenylanilide, 4,4'-ditoluene sulfoxide, 4,4'-dichlorophenyl sulfoxide, methyl phenyl sulfoxide, dibenzyl sulfoxide and benzenesulfenyl chloride.
[0010] The purity of the phenyl sulfoxide organic compound is ≥98%.
[0011] An application of the electrolyte additive is application of the additive as an additive in an alkali metal-thionyl chloride secondary battery electrolyte.
[0012] An alkali metal-thionyl chloride secondary battery electrolyte, the electrolyte comprising a salt capable of transmitting alkali metal ions, thionyl chloride, and the additive; the concentration of the additive in the electrolyte is 0.05-1.0 mol / L, and the concentration of the salt capable of transmitting alkali metal ions in the electrolyte is 0.5-4 mol / L, preferably 1-2 mol / L.
[0013] The salt capable of transmitting alkali metal ions is an alkali metal salt and / or aluminum trichloride.
[0014] The anion of the alkali metal salt is tetrachloroaluminate, tetrafluoroborate, dioxalatoborate, difluorooxalatoborate, bistrifluoromethylsulfonyl imide, trifluoromethylsulfonate, bisfluorosulfonyl imide, tetrachlorogallate or perchlorate; the cation of the alkali metal salt is lithium ion, sodium ion or potassium ion.
[0015] The purity of the salt capable of transporting alkali metal ions is ≥ 99%.
[0016] The purity of the thionyl chloride is ≥99.5%.
[0017] Preparation of the electrolyte:
[0018] (1) dissolving the desired transportable alkali metal ion salt in thionyl chloride to obtain a uniform solution;
[0019] (2) Dissolving the additive in the above solution and stirring evenly to obtain the desired electrolyte.
[0020] An application of the electrolyte is application of the electrolyte in an alkali metal-thionyl chloride secondary battery.
[0021] The electrolyte with the additive added is used as the electrolyte of an alkali metal-thionyl chloride secondary battery with a carbon material as a positive electrode.
[0022] An alkali metal-thionyl chloride secondary battery comprises a positive electrode, a negative electrode and the electrolyte.
[0023] The active material of the positive electrode is one or more of graphite, Super P, acetylene black, Ketjen black, carbon nanotubes, and carbon fibers; the current collector of the positive electrode is stainless steel; and the negative electrode is one or more of lithium metal, sodium metal, potassium metal, lithium silicon alloy, sodium silicon alloy, lithium tin alloy, sodium tin alloy, and lithium sodium alloy.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. The phenylsulfoxide organic additive proposed in the present invention can effectively increase the discharge voltage of the battery and can withstand high-rate discharge. Regarding its discharge reduction mechanism, specifically, the additive molecules adsorbed on the carbon are reduced by electrons and decomposed into sulfoxide free radicals and benzene anions. The sulfoxide free radicals are decomposed into sulfur dioxide and sulfur by dimerization. The benzene anions attack the thionyl chloride solvent molecules to reform the additive with a phenylsulfoxide structure, while releasing chloride ions to form lithium chloride. In short, when there is no additive, thionyl chloride is directly reduced by electrons; when there is an additive, thionyl chloride decomposes by chemical reduction (the additive molecules are reduced by electrons, and their products attack thionyl chloride). Therefore, the additive has the characteristics of a redox mediator during discharge reduction.
[0026] 2. The phenylsulfoxide organic additive proposed in the present invention can realize the secondary use of the battery, significantly reduce the charging voltage of the battery, and improve the energy efficiency. Compared with organic amine salt additives, it has better improvement effect in charge and discharge polarization. Regarding its charging oxidation mechanism, it is completely different from the reaction mechanism without additives. Specifically, when there is no additive, the lithium chloride deposited on the carbon loses electrons and oxidizes to chlorine, and the chlorine combines with the discharge products sulfur and sulfur dioxide. The combined product is further reacted and converted into thionyl chloride to achieve reversible transformation, but the conversion efficiency is low and it is irreversible. When the phenylsulfoxide organic additive is present, it will oxidize at a lower potential to become a phenylsulfoxide cation and directly oxidize the alkali metal chloride (discharge product) to generate thionyl chloride and benzene cations. The benzene cation further reacts with sulfur and sulfur dioxide to regenerate an additive with a phenylsulfoxide structure. The relevant conversion reaction efficiency is higher and can be used twice. In short, the phenylsulfoxide organic additive has the properties of a redox mediator for lithium-oxygen batteries. The additive can achieve a cycle life with a longer stable time, which means that the additive does have the advantage of low cycle loss.
[0027] 3. The preparation process of the present invention by introducing additives into the alkali metal-thionyl chloride electrolyte is simple, the preparation cycle is short, the preparation equipment is simple and easy to operate, and it is convenient for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a charge and discharge curve diagram of the additive-free electrolyte provided in Example 1 of the present invention.
[0029] Figure 2 This is a charge and discharge curve diagram of the electrolyte with additives provided in Example 1 of the present invention.
[0030] Figure 3 This is a discharge curve diagram of the additive-free electrolyte provided in Example 1 of the present invention at different currents.
[0031] Figure 4This is a discharge curve diagram of the electrolyte with additives at different currents provided in Example 1 of the present invention.
[0032] Figure 5 The cycle diagram of the battery corresponding to the electrolyte with additives provided in Example 1 of the present invention.
[0033] Figure 6 This is a charge and discharge curve diagram of the electrolyte with additives provided in Example 2 of the present invention.
[0034] Figure 7 The cycle diagram of the battery corresponding to the electrolyte with additives provided in Example 2 of the present invention.
[0035] Figure 8 This is a charge and discharge curve diagram of the electrolyte with additives provided in Example 3 of the present invention.
[0036] Fig. 9 The cycle diagram of the battery corresponding to the electrolyte with additives provided in Example 3 of the present invention.
[0037] Fig.10 This is a charge and discharge curve diagram of the additive-free electrolyte provided in Example 4 of the present invention.
[0038] Fig.11 This is a charge and discharge curve diagram of the electrolyte with additives provided in Example 4 of the present invention.
[0039] Fig.12 The cycle diagram of the battery corresponding to the electrolyte with additives provided in Example 4 of the present invention. DETAILED DESCRIPTION
[0040] The present invention will be further described in detail below in conjunction with the examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0041] The additive introduced in the present invention acts as a redox mediator, which first undergoes reduction / oxidation, and can significantly improve the discharge / charge performance. The battery using the additive provided by the present invention can improve the discharge platform potential and capacity at high current density, significantly improve the voltage hysteresis phenomenon, and thus obtain better specific energy and energy efficiency. Compared with the control sample without the additive, the battery using the additive provided by the present invention has significantly reduced charge and discharge polarization, improved rate performance, and achieved secondary stable cycle. After 100 cycles, the cycle capacity retention rate is significant.
[0042] The reagents used in the following examples are all commercially available products, wherein the purity of phenyl sulfoxide organics is ≥98%; the purity of salts capable of transmitting alkali metal ions is ≥99%; and the purity of SOCl2 is ≥99.5%.
[0043] The electrochemical performance testing conditions in the following examples are:
[0044] (1) Single discharge rate test: discharge cut-off voltage is 2V, discharge current is 1A -1 , 20Ag -1 , 30Ag -1 .
[0045] (2) Cyclic test: using a high loading (10 mg cm -2 ) positive electrode, cycle data charge cut-off capacity is 6mA cm -2 , discharge cut-off voltage is 2V, discharge current is 5mAcm -2 The charge and discharge voltage curve is displayed by taking one circle.
[0046] Example 1
[0047] Control group battery:
[0048] (1) Preparation of electrolyte: 42 g of lithium tetrachloroaluminate was added to 100 mL of distilled and purified SOCl2 and stirred for 2 h to obtain an electrolyte;
[0049] (2) Battery assembly: In a conventional manner, the Super P material was scraped onto a stainless steel foil as a working electrode, a metal lithium sheet was used as a counter electrode, and a battery was assembled with the above electrolyte as a control group, and its electrochemical performance was tested ( Figure 1 and Figure 3 ).
[0050] Experimental battery:
[0051] (1) Preparation of electrolyte: 42 g of lithium tetrachloroaluminate was added to 100 mL of distilled and purified SOCl2 and stirred for 2 h to obtain a mixed solution, and then 0.2 mol / L of 4,4'-ditoluene sulfoxide was added to the mixed solution to obtain an electrolyte.
[0052] (2) Battery assembly: In a conventional manner, the Super P material was scraped onto a stainless steel foil as a working electrode, a metal lithium sheet was used as a counter electrode, and the battery was assembled with the above electrolyte as an experimental group, and its electrochemical performance was tested ( Figure 2 , Figure 4 and Figure 5 ).
[0053] It can be seen from the above tests that compared with the control group, the experimental group achieved a significant reduction in charge and discharge voltage polarization and can be used stably at a high rate. Since the introduced additive acts as a redox mediator, it will first undergo reduction / oxidation: (1) During the discharge process, it preferentially obtains electron reduction to avoid the occurrence of dimerization hindrance during the electrochemical reduction of thionyl chloride; (2) During the charging process, it preferentially loses electrons to avoid the occurrence of inefficient conversion pathways mediated by chlorine gas; thereby achieving improved discharge / charge performance. In addition, the reduction potential of the additive is higher, and the adsorption of lithium ions by the charge-rich π bond system improves the voltage hysteresis phenomenon, so it has a higher discharge platform potential and capacity at high current density (the discharge platform voltage of the battery introduced with the additive is higher than 3V at high current), thereby significantly obtaining better specific energy and energy efficiency. And it has achieved a secondary stable cycle ( Figure 5 ), after 100 cycles, the cycle capacity retention rate can reach 97%. However, the high-load positive electrode without additives cannot be cycled at all ( Figure 1 ), so the introduction of additives successfully transformed the primary battery into a high-power secondary battery.
[0054] Example 2
[0055] Control group battery:
[0056] (1) Preparation of electrolyte: Add 29 g of aluminum chloride to 100 mL of distilled and purified SOCl2 and stir for 2 h to obtain an electrolyte;
[0057] (2) Battery assembly: In a conventional manner, acetylene black material was scraped onto a stainless steel foil as a working electrode, a metal lithium sheet was used as a counter electrode, and a battery was assembled with the above electrolyte as a control group, and its electrochemical performance was tested.
[0058] Experimental battery:
[0059] (1) Preparation of electrolyte: 29 g of aluminum chloride was added to 100 mL of distilled and purified SOCl2 and stirred for 2 h to obtain a mixed solution, and then 0.2 mol / L of N-sulfenylaniline was added to the mixed solution to obtain an electrolyte.
[0060] (2) Battery assembly: According to the conventional method, acetylene black material was scraped onto stainless steel foil as the working electrode, and the metal lithium sheet was used as the counter electrode. The battery was assembled with the above electrolyte as the experimental group, and its electrochemical performance was tested ( Figure 6 , Figure 7 ).
[0061] The experimental group also achieved a significant reduction in charge and discharge voltage polarization and realized secondary stable cycles. After 100 cycles, the cycle capacity retention rate reached 97%.
[0062] Example 3
[0063] Control group battery:
[0064] (1) Preparation of electrolyte: 42 g of lithium tetrachloroaluminate and 29 g of aluminum trichloride were added to 100 mL of distilled and purified SOCl2 and stirred for 2 h to obtain an electrolyte;
[0065] (2) Battery assembly: In a conventional manner, the Ketjen black material was scraped onto a stainless steel foil as a working electrode, a metal lithium sheet was used as a counter electrode, and a battery was assembled with the above-mentioned electrolyte as a control group, and its electrochemical performance was tested.
[0066] Experimental battery:
[0067] (1) Preparation of electrolyte: 42 g of lithium tetrachloroaluminate and 29 g of aluminum trichloride were added to 100 mL of distilled and purified SOCl2 and stirred for 2 h to obtain a mixed solution, and then 0.2 mol / L of diphenyl sulfoxide was added to the mixed solution to obtain an electrolyte.
[0068] (2) Battery assembly: In a conventional manner, the Ketjen black material was scraped onto a stainless steel foil as a working electrode, a metal lithium sheet was used as a counter electrode, and the battery was assembled with the above electrolyte to form an experimental group, and its electrochemical performance was tested ( Figure 8 , Fig. 9 ).
[0069] The experimental group also achieved a significant reduction in charge and discharge voltage polarization, and its cycle stability was greatly improved. After 100 cycles, the cycle capacity retention rate could reach 95%.
[0070] Example 4
[0071] Control group battery:
[0072] (1) Preparation of electrolyte: 42 g of sodium tetrachloroaluminate was added to 100 mL of distilled and purified SOCl2 and stirred for 2 h to obtain an electrolyte;
[0073] (2) Battery assembly: According to the conventional method, acetylene black material was scraped onto stainless steel foil as the working electrode, and the metal sodium sheet was used as the counter electrode. The battery was assembled with the above electrolyte as the control group, and its electrochemical performance was tested ( Fig.10 ).
[0074] Experimental battery:
[0075] (1) Preparation of electrolyte: 42 g of sodium tetrachloroaluminate was added to 100 mL of distilled and purified SOCl2 and stirred for 2 h to obtain a mixed solution, and then 0.2 mol / L of 4,4'-ditoluene sulfoxide was added to the mixed solution to obtain an electrolyte.
[0076] (2) Battery assembly: According to the conventional method, acetylene black material was scraped onto stainless steel foil as the working electrode, and the metal sodium sheet was used as the counter electrode. The battery was assembled with the above electrolyte as the experimental group, and its electrochemical performance was tested ( Fig.11 , Fig.12 ).
[0077] The experimental group also achieved a significant reduction in charge and discharge voltage polarization and secondary cycling. After 100 cycles, the cycle capacity retention rate reached 99%.
[0078] As can be seen from the above embodiments, the introduction of the additive of the present invention changes the redox couple at the carbon positive electrode interface, can significantly improve the discharge platform at high current density and improve the battery polarization, so that the alkali metal-thionyl chloride secondary battery has a good discharge voltage and discharge capacity, and significantly improves the voltage hysteresis of the alkali metal-thionyl chloride secondary battery. The battery using the additive provided by the present invention has a significantly improved discharge voltage and rate performance compared to the control sample without the additive, and realizes a secondary stable cycle. After 100 cycles, the cycle capacity retention rate is significant.
[0079] The above are only preferred specific embodiments of the present invention, but the protection scope of the invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.
Claims
1. An electrolyte additive for an alkali metal-thionyl chloride secondary battery, characterized in that: The additive in the electrolyte for alkali metal-thionyl chloride secondary battery is organic matter containing phenyl sulfoxide; the concentration of the additive in the electrolyte is 0.05-1.0 mol / L.
2. The electrolyte additive for alkali metal-thionyl chloride secondary batteries according to claim 1, characterized in that: The phenyl sulfoxide organic compound is one or more of diphenyl sulfoxide, N-sulfenylanilide, 4,4'-ditoluene sulfoxide, 4,4'-dichlorophenyl sulfoxide, methyl phenyl sulfoxide, dibenzyl sulfoxide and benzenesulfenyl chloride.
3. An application of the electrolyte additive for alkali metal-thionyl chloride secondary batteries according to claim 1, characterized in that: The additive is used as an additive in an alkali metal-thionyl chloride secondary battery electrolyte.
4. An alkali metal-thionyl chloride secondary battery electrolyte, characterized in that: The electrolyte comprises a salt capable of transmitting alkali metal ions, thionyl chloride, and the additive according to claim 1; the concentration of the additive in the electrolyte is 0.05-1.0 mol / L, and the concentration of the salt capable of transmitting alkali metal ions in the electrolyte is 0.5-4 mol / L.
5. The alkali metal-thionyl chloride secondary battery electrolyte according to claim 4, characterized in that: The salt capable of transmitting alkali metal ions is alkali metal salt and / or aluminum chloride.
6. The alkali metal-thionyl chloride secondary battery electrolyte according to claim 5, characterized in that: The anion of the alkali metal salt is tetrachloroaluminate, tetrafluoroborate, dioxalatoborate, difluorooxalatoborate, bistrifluoromethylsulfonyl imide, trifluoromethylsulfonate, bisfluorosulfonyl imide, tetrachlorogallate or perchlorate; the cation of the alkali metal salt is lithium ion, sodium ion or potassium ion.
7. An application of the electrolyte according to claim 4, characterized in that: Application of the electrolyte in an alkali metal-thionyl chloride secondary battery.
8. An alkali metal-thionyl chloride secondary battery, characterized in that: The battery comprises a positive electrode, a negative electrode and the electrolyte according to claim 4.
9. The alkali metal-thionyl chloride secondary battery according to claim 8, characterized in that: The active material of the positive electrode is one or more of graphite, Super P, acetylene black, Ketjen black, carbon nanotubes, and carbon fibers; the current collector of the positive electrode is stainless steel; and the negative electrode is one or more of lithium metal, sodium metal, potassium metal, lithium silicon alloy, sodium silicon alloy, lithium tin alloy, sodium tin alloy, and lithium sodium alloy.